Tradition-Based Community Education Model: The Effectiveness of Maddengeng in Ecological Conflict Resolution - Amiruddin Amiruddin; Syamsul Bahri; Muh. Adnan Yusuf; Hermansyah Hermansyah; Resky Rahmadani; Dias Sanubari; Jesiqa Putri Amanda; Besse Agusnaeni; Besse Putri Ummiahani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The conversion of forest land into maize plantations in Labissa Village during 2010–2011 disrupted the local ecosystem, triggering a surge in the wild boar (Sus scrofa) population and intensifying human–wildlife ecological conflict. This condition threatened household food security and underscored the urgency of transmitting indigenous ecological knowledge to younger generations before culturally rooted solutions are lost. This study analyzes the Maddengeng tradition as a community-based education model grounded in local wisdom for mitigating ecological conflict. A qualitative phenomenological case-study design was employed, combining in-depth interviews and participatory observation. Informants were selected through purposive sampling and comprised affected residents, customary authority figures (tokoh adat), and senior high school students. Data trustworthiness was established through source and method triangulation, and data were analyzed using an interactive model of reduction, display, and conclusion drawing. Findings indicate that Maddengeng has transformed from a subsistence hunting practice into an adaptive social-learning institution. For residents and customary leaders, the tradition strengthens social cohesion and facilitates conflict resolution; for senior high school students, participation functions as contextual character education and a vehicle for the transmission of local wisdom outside formal schooling. Theoretically and practically, this study contributes to the development of community-based education models that integrate indigenous knowledge into the informal curriculum for youth. It offers a sustainable pathway for maintaining ecological harmony, food security, and cultural identity preservation in Bone Regency, Indonesia.